KECERNAAN PROTEIN BIJI KAPUK (Ceiba petandra G) SECARA IN VITRO UNTUK PAKAN IKAN - Fitry Primadona; Supriyono Eko Wardoyo; O. D. Subhakti Hasan (JURNAL SAINS NATURAL, 2013)
Protein Digestibility of Kapok Seeds in Vitro for Fish Feed        Kapok seeds is a by-product of agricultural industry having potential to be used as raw material for fish feed as a source of protein and essential fats. The content of the protein in the kapok seed  flour is 28 – 34 % that is an overwhelming amount to be a great source of protein for fish feed. Feasibility studies are needed, however, the use of kapok seed based on the digestibility of the protein. Pepsin with concentrations of 0.02; 0.2; and 2 % (in 0.075 N HCl solution) kapok seed flour added in three repetitions to test the digestibility of kapok seed invitro. Undigested protein was then analyzed using the kjeldahl method. Determination optimal concentration of pepsin was calculated based on the remaining undigested proteins (pepsin indigest) and compared the amount of protein digestibility of proteins obtained before (pepsin digest). The research results revealed that to digestibility of protein on concentration of 0.02; 0,20 and 2,0 % was 64,43; 68,42; 65,33%. Statistical test Anova revealed any significant differences of treatment respectively of  protein digestibility. Test of Least Square Difference (LSD) stated that each  treatment significantly different. Concentration optimum of enzyme that givethe best digestibility value was 0.20 % digestibility values 68,43% in the level of  error 0.05.Keywords : Kapok seed flour, protein, pepsin, invitro, optimum digestibility, proximate analysis ABSTRAK          Biji kapuk merupakan hasil samping industri pertanian yang berpotensi untuk dijadikan bahan baku pakan ikan sebagai sumber protein dan sumber lemak esensial. Komposisi protein pada tepung biji kapuk sebesar 28‑34% adalah jumlah yang sangat potensial untuk dijadikan sumber protein bagi pakan ikan. Akan tetapi diperlukan kajian kelayakan penggunaan biji kapuk berdasarkan kecernaan protein.Pepsin dengan konsentrasi 0,02; 0,2; dan  2%(larutan dalam HCl 0,075 N) ditambahkan pada tepung biji kapuk dengan tiga kali pengulangan untuk menguji kecernaan biji kapuk secara invitro. Protein yang tercerna kemudian dianalisis menggunakan metode kjeldahl. Penentukan konsentrasi  pepsin optimal dihitung berdasarkan sisa protein yang tidak tercerna(pepsin indigest) dan dibandingkan jumlah protein awal sehingga didapatkan kecernaan protein (pepsin digest).Hasil penelitian menyatakan kecernaan protein pada  konsentrasi 0,02;0,2%;dan 2%  berturut turut 64,43; 68,42; 65,33%. Uji statistik Anova menyatakan setiap perlakuan memberikan perbedaan yang signifikan terhadap kecernaan protein. Uji Least Square Difference (LSD) menyatakan setiap perbandingan perlakuan berbeda. Konsentrasi enzim optimum yang memberikan nilai kecernaan terbaik adalah 0,20% (68,43%) pada tingkat kesalahan 0,05.Kata kunci: Tepung biji kapuk, protein, pepsin, invitro, kecernaan optimum, proksimat